FACTORS AFFECTING INTENTION OF JOB QUITTING AMONG UNIVERSITY LECTURERS IN VIETNAM - Hoàng Thị Thanh Chung (Tạp chí Khoa học Đại học Đà Lạt)
This study analyzes different factors affecting the intention of job quitting among university lecturers in Vietnam. The primary objective is to analyze the impact of job stress, job satisfaction and organizational commitment on the intention of job quitting. Findings from a survey sample of 242 respondent lecturers showed that public university lecturers are generally less satisfied with their jobs, less stressed with their jobs and also have higher commitment to their institutions than private university lecturers. The results of this study provide the theoretical and practical implications for policy formulation in the context in which brain drain from higher education institutions to other economic sectors is getting more severe and has been affecting the overall development of the education system.